قراءة فى ديوان رياض الجنة ونور الدجنة للشيخ عبدالرحيم البرعى - محمد، كمال حامد عبدالله (جامعة كسلا, 2016)
The study was about reading of Alburee poems’ that called (Ryad alganna and Nour Aldagana) which composed of three axes: the first was Alburee biography, the second was described the collection of poems and finally was about poet style and his language .The important objective of (he study was to show the poetical of Alburee, The important of this study is show the religious message which act in Ryad alganna and Nour Aldagana and Eulogizes poems, which has effects to increase the religious behavior through showing the prophetic curriculum and its recommendations , also the study is very important source to Arabian library with its special arts. The researcher adopted a methodical description in this study to show some poetic samples by studies and analyses. The important findings of the study are as follows: Alburee was distinguished with his specific style organization that was not adopted by Eulogizes in Sudan. An Alburee poem is a new school in art religious poetry. Alburee was un like mysticism approach. Alburees method was free of philosophical ideas which used by other religious poets before.
تناولت الدراسة موضوع قراءة في ديوان رياض الجنة ونور الدجنة لعبد الرحيم البرعي السوداني، وقد دارت حول ثلاثة مباحث، حيث جاء المبحث الأول بعنوان، سيرة الشيخ البرعي، أما الثاني فتناول وصف الديوان، وكان المبحث الأخير بعنوان لغة الشاعر وأسلوبه، هذا ومن أهم أهداف الدراسة إبراز شاعرية البرعي من خلال هذا الديوان، وتتمثل أهمية الدراسة في أهمية الرسالة الدينية المتمثلة في الديوان بصورة خاصة وأهمية شعر المديح الديني بصفة عامة لما له من آثار في ترقية السلوك الديني من خلال عرض السيرة النبوية وما يتخللها من مواعظ، وكذلك رفد المكتبة العربية بنتاج أدبي ذي لون خاص. وقد وظف الباحث المنهج الوصفي من خلال عرض بعض النماذج الشعرية دراسة وتحليلا، أما من أهم النتائج التي توصلت لها الدراسة، فتمثلت في الآتي: تميز البرعي بخصوصية الأسلوب وطريقة نظم لم يسبق إليها أحد من المداح في السودان، ما يجعلها مدرسة جديدة في فن الشعر الديني. قد خلا شعر البرعي من الأفكار الفلسفية التي اتسم بها شعراء التصوف من قبله.
Keywords: الادب العربى -- الشعر العربى -- ديوان رياض الجنة ونور الدجنة -- النقد الادبى -- البرعي، عبدالرحيم بن الشيخ محمد وقيع الله، ت. 2005 م